Earth as an evolving planetary system - Condie, Kent C. (Academic Press, 2021)
Earth as an Evolving Planetary System, Fourth Edition, examines the various subsystems that play a role in the evolution of the Earth, including subsystems in the crust, mantle, core, atmosphere, oceans, and life. This new edition includes over 100 new pages of material, data, and images. New topics include a new chapter on orogens and orogenic crust, as well as expanded coverage of oceanic topics. The Earth's atmosphere, hydrosphere, and biosphere, crustal and mantle evolution, the supercontinent cycle, great events in Earth history, and the Earth in comparison to other planets are also covered. Earth as an Evolving Planetary System, Fourth Edition is a key reference for students and researchers in the Earth and planetary scientists, especially for geologists, geophysicists, and geochemists.